Genome-wide identification and analysis of the cytokinin oxidase/dehydrogenase (ckx) gene family in finger millet (Eleusine coracana) - Blume, Rostyslav; Yemets, Alla; Korkhovyi, Vitaliy; Radchuk, Volodymyr; Rakhmetov, Dzhamal; Blume, Yaroslav (Frontiers in Genetics, 2022)
Cytokinin dehydrogenase/oxidase (CKX) enzymes play a key role in regulating cytokinin (CK) levels in plants by degrading the excess of this phytohormone. CKX genes have proven an attractive target for genetic engineering, as their silencing boosts cytokinin accumulation in various tissues, thereby contributing to a rapid increase in biomass and overall plant productivity. We previously reported a similar effect in finger millet (Eleusine coracana) somaclonal lines, caused by downregulation of EcCKX1 and EcCKX2. However, the CKX gene family has numerous representatives, especially in allopolyploid crop species, such as E. coracana. To date, the entire CKX gene family of E. coracana and its related species has not been characterized. We offer here, for the first time, a comprehensive genome-wide identification and analysis of a panel of CKX genes in finger millet. The functional genes identified in the E. coracana genome are compared with the previously-identified genes, EcCKX1 and EcCKX2. Exon-intron structural analysis and motif analysis of FAD- and CK-binding domains are performed. The phylogeny of the EcCKX genes suggests that CKX genes are divided into several distinct groups, corresponding to certain isotypes. Finally, the phenotypic effect of EcCKX1 and EcCKX2 in partially silencing the SE7 somaclonal line is investigated, showing that lines deficient in CKX-expression demonstrate increased grain yield and greater bushiness, enhanced biomass accumulation, and a shorter vegetation cycle.